Synthesis, Characterization, and Antimicrobial Activity of Novel Sulfonated Copper-Triazine Complexes - Katugampala, Supun; Perera, Inoka C.; Nanayakkara, Chandrika; Perera, Theshini (My University, 2018)
Metallotriazine complexes possess interesting biological and medicinal properties, and the present study focuses on the synthesis, characterization, and antimicrobial activity of four novel copper-triazine derivatives in search of potent antibacterial and antifungal drug leads. In this study, 3-(2-pyridyl)-5,6-diphenyl-1,2,4-triazine-4,4′-disulfonic acid monosodium salt (L1, ferrozine) and 3-(2-pyridyl)-5,6-di(2-furyl)-1,2,4-triazine-5,5′-disulfonic acid disodium salt (L2, ferene) have been used as ligands to study the complexation towards copper(II). The synthesized complexes, [CuCl2(ferrozine)]·7H2O·MeOH (1), [CuCl2(ferrozine)2]·5H2O·MeOH (2), [CuCl2(ferene)]·H2O·MeOH (3), and [CuCl2(ferene)2]·H2O·MeOH (4), have been characterized spectroscopically, and preliminary bioassays have been carried out. FTIR spectroscopic data have shown that N=N and C=N stretching frequencies of complexes have been shifted towards lower frequencies in comparison with that of the ligands, confirming new bond formation between Cu and N, which in turn lowers the strength of N=N and C=N bonds. In addition, a bathochromic shift has been observed for UV-visible spectra of complexes (1), (2), (3), and (4). Furthermore, elemental analysis data have been useful to obtain empirical formulas of these complexes and to establish the purity of each complex. Complexes (1) and (2) have shown antibacterial activity for both S. aureus (ATCC® 25923) and E. coli (ATCC® 25922) at 1 mg/disc concentration, and ferrozine has shown a larger inhibition zone against the clinical sample of C. albicans at 1 mg/disc concentration in comparison with the positive control, fluconazole.